Biochar dielectric material and preparation method thereof

By carbonizing cotton straw under high temperature and low oxygen conditions and mixing it with additives, biochar dielectric materials with excellent dielectric properties are prepared, which solves the problem of low utilization rate of cotton straw and achieves the effect of resource utilization and environmental protection.

CN119701871APending Publication Date: 2025-03-28XINJIANG AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411916268.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The low utilization rate of cotton straw leads to ecological environment pollution and waste of resources, and it is difficult for the existing technology to effectively convert it into valuable products.

Method used

Biochar is prepared by carbonizing cotton straw under high temperature and low oxygen conditions, and mixed with additives such as SiO2 and Al2O3 to prepare biochar dielectric materials with excellent dielectric properties.

Benefits of technology

It improves the performance and economic benefits of dielectric materials, reduces environmental pollution and resource waste, and provides a resource utilization solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701871A_ABST
    Figure CN119701871A_ABST
Patent Text Reader

Abstract

The invention discloses a biochar dielectric material and a preparation method thereof, and belongs to the technical field of dielectric materials. According to the invention, crop straws are carbonized into biochar under high-temperature and low-oxygen conditions, and the biochar is mixed with an additive to obtain a dielectric material with excellent thermal stability and dielectric properties; the preparation method of the material is simple and easy to implement, the raw materials are low in price and easy to obtain, large-scale production is easy, waste is reduced, meanwhile, the resource utilization efficiency is improved, the environmental burden is reduced, and the material has excellent industrial prospects and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dielectric materials, and specifically relates to a biochar dielectric material and a preparation method thereof. Background Art

[0002] Cotton is the most economic crop with the largest scale planting advantage in Xinjiang. In 2022, Xinjiang's cotton output accounted for 90.2% of the national total. The cotton industry is a strong support for Xinjiang's economic development. However, the low utilization rate of the large amount of cotton straw produced not only causes serious pollution to the ecological environment, but also threatens people's physical and mental health, and poses a great challenge to the resource utilization and pollution prevention and control of farmland waste. By converting straw into products or resources with economic value, waste can be reduced, resource utilization efficiency can be improved, and the environmental burden can be reduced. Studies have found that preparing biochar through high-temperature and low-oxygen carbonization of cotton straw, and adding different proportions of nitrogen, phosphorus and potassium fertilizers to prepare biomass charcoal-based fertilizers are important ways to achieve high-value conversion of straw in Xinjiang.

[0003] Biochar (BC) is usually a carbon-rich material made by pyrolyzing biomass under anaerobic conditions (<700℃) in a state of complete or partial anoxic pyrolysis. Mainly composed of elements such as carbon (C), hydrogen (H) and oxygen (O), biochar has a wide range of applications in agriculture and soil improvement due to its high environmental stability and strong ion exchange properties. This carbon material can not only improve soil structure and promote plant growth, but also help to improve the water retention capacity and nutrient retention in the soil. The preparation process of biochar emphasizes the special conditions of pyrolysis to ensure that the final product has ideal physical and chemical properties to better meet the needs of agricultural production. Its unique structure and performance characteristics enable it to adsorb water, nutrients and microorganisms, thereby significantly improving the water retention, aeration and fertility of the soil, and helping to alleviate the problems of soil drought and nutrient loss. Biochar can also provide an ideal microbial environment and promote the growth of beneficial microorganisms, thereby enhancing the health of the soil. Biochar can increase the ion exchange capacity of the soil, enhance the soil's retention and release of nutrients, help improve the utilization efficiency of nitrogen fertilizers, and reduce dependence on chemical fertilizers. Biochar has a stable carbon structure in the soil, which can increase the storage of soil organic carbon, help improve soil structure, increase water retention, and promote microbial activity, thereby improving soil productivity. These characteristics make biochar a powerful tool in agriculture and soil management, helping to improve soil quality and increase crop yields. It also helps to reduce the use of fertilizers and water resources, while reducing negative impacts on the environment. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a biochar dielectric material and a preparation method thereof, which provides ideas for the application of biochar in dielectric materials.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a biochar dielectric material, comprising the following steps:

[0006] S1: S1: The crop straw was cleaned and cut into small pieces of 10 cm in length, and NaHCO3 was added and mixed, and pyrolyzed for 2 to 3 h;

[0007] S2: After pyrolysis, the temperature is lowered to room temperature at a rate of 10-15°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized product;

[0008] S3: Mixing the carbide with the additive to obtain a biochar dielectric material.

[0009] The beneficial effects of the present invention are as follows: the present invention utilizes crop straw to prepare biochar, the biochar has a large specific surface area and a developed pore structure, which is conducive to the storage and transmission of charges in the material, and using it as a raw material for preparing dielectric materials helps to improve the performance of dielectric materials; secondly, the preparation method of the present invention is simple and easy, the raw materials are cheap and easily available, and it has excellent economic benefits and industrial prospects.

[0010] Based on the above technical solution, the present invention can also be improved as follows.

[0011] Furthermore, the crop straw is cotton straw.

[0012] Furthermore, the mass ratio of crop straw to NaHCO3 is 50-60:1.

[0013] The beneficial effects of adopting further technical solutions are: the use of cotton straw avoids serious pollution to the ecological environment, and at the same time, farmland waste is utilized as a resource; NaHCO3 can neutralize some acidic functional groups on the surface of biochar during the preparation of biochar, thereby changing the surface properties of biochar, making it have a higher specific surface area and a richer pore structure, which is beneficial to improving its adsorption performance and dielectric properties.

[0014] Furthermore, the pyrolysis is carried out by heating the temperature from room temperature to 100-600° C. at a heating rate of 10-15° C. / min.

[0015] The beneficial effect of adopting a further technical solution is that within this temperature range, the organizational form of the organic components of cotton straw changes during anaerobic pyrolysis, accompanied by the breaking of long chains, the elemental composition of the obtained biochar is stable, and the structure is a deformed rectangular and honeycomb pore structure, which increases the surface area of ​​the biochar and helps to improve the performance of the dielectric material.

[0016] Furthermore, the mass ratio of carbide to additive is 9 to 12:1.

[0017] Furthermore, the additive is a mixture of SiO2 and Al2O3.

[0018] Furthermore, the mass ratio of SiO2 and Al2O3 is 1-2:0.5-1.

[0019] The beneficial effects of adopting further technical solutions are: SiO2 has the characteristics of high melting point, high hardness, good insulation and corrosion resistance, which can effectively enhance the insulation performance and stability of dielectric materials; Al2O3 has high surface activity, excellent hydrophilicity and thermal stability, and can stabilize the dielectric properties of dielectric materials by improving the carbide microstructure.

[0020] The invention also provides a biochar dielectric material prepared by the method for preparing the biochar dielectric material.

[0021] The beneficial effects of the present invention are as follows: under high temperature and low oxygen conditions, the present invention obtains a dielectric anomaly functional material by carbonizing crop straw, which has the characteristics of thermal stability and excellent dielectric properties; and by converting the straw into a dielectric material with economic value, waste is reduced, resource utilization efficiency is improved, and the environmental burden is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the SEM image of BC1-6 in Examples 1-6;

[0023] Figure 2 XRD patterns of BC1 to 6 in Examples 1 to 6;

[0024] Figure 3 TG diagrams of BC1 to 6 in Examples 1 to 6;

[0025] Figure 4 It is the DTG diagram of BC1-6 in Examples 1-6;

[0026] Figure 5 This is a temperature-increasing dielectric test diagram of the biochar dielectric material prepared in Example 1;

[0027] Figure 6 This is a temperature-increasing dielectric test diagram of the biochar dielectric material prepared in Example 2;

[0028] Figure 7 Temperature-increasing dielectric test of the biochar dielectric material prepared in Example 3 Figure 1 ;

[0029] Figure 8 Temperature-increasing dielectric test of the biochar dielectric material prepared in Example 3 Figure 2 ;

[0030] Fig. 9 This is a temperature-increasing dielectric test diagram of the biochar dielectric material prepared in Example 4;

[0031] Fig.10 This is a temperature-increasing dielectric test diagram of the biochar dielectric material prepared in Example 5;

[0032] Fig.11 This is a temperature-increasing dielectric test diagram of the biochar dielectric material prepared in Example 6. DETAILED DESCRIPTION

[0033] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0034] Example 1

[0035] A method for preparing a biochar dielectric material comprises the following steps:

[0036] S1: Wash and cut cotton straw into 10 cm long segments, add NaHCO3 and mix, the mass ratio of cotton straw to NaHCO3 is 55:1, then heat from room temperature to 100 °C at a heating rate of 10 °C / min, and carbonize at constant temperature for 2.5 h;

[0037] S2: After constant temperature carbonization, the temperature is lowered to room temperature at a rate of 10°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized product BC1;

[0038] S3: The carbide and the additive (a mixture of SiO2 and Al2O3, with a mass ratio of 1.5:0.8) are uniformly mixed in a mass ratio of 10:1 to obtain a biochar dielectric material.

[0039] Example 2

[0040] S1: Wash and cut cotton straw into 10 cm long segments, add NaHCO3 and mix, the mass ratio of cotton straw to NaHCO3 is 50:1, then heat from room temperature to 200 °C at a heating rate of 15 °C / min, and carbonize at constant temperature for 2 h;

[0041] S2: After constant temperature carbonization, the temperature is lowered to room temperature at a rate of 15°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized product BC2;

[0042] S3: The carbide and the additive (a mixture of SiO2 and Al2O3, with a mass ratio of 1:1) are uniformly mixed in a mass ratio of 9:1 to obtain a biochar dielectric material.

[0043] Example 3

[0044] S1: Wash and cut cotton straw into 10 cm long segments, add NaHCO3 and mix, the mass ratio of cotton straw to NaHCO3 is 60:1, then heat from room temperature to 300℃ at a heating rate of 10℃ / min, and carbonize at constant temperature for 3h;

[0045] S2: After constant temperature carbonization, the temperature is lowered to room temperature at a rate of 10°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized product BC3;

[0046] S3: The carbide and the additive (a mixture of SiO2 and Al2O3, with a mass ratio of 2:0.5) are uniformly mixed in a mass ratio of 12:1 to obtain a biochar dielectric material.

[0047] Example 4

[0048] S1: Wash and cut cotton straw into 10 cm long segments, add NaHCO3 and mix, the mass ratio of cotton straw to NaHCO3 is 55:1, then heat from room temperature to 400℃ at a heating rate of 10℃ / min, and carbonize at constant temperature for 2.5h;

[0049] S2: After constant temperature carbonization, the temperature is lowered to room temperature at a rate of 10°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized product BC4;

[0050] S3: The carbide and the additive (a mixture of SiO2 and Al2O3, with a mass ratio of 1.5:0.8) are uniformly mixed in a mass ratio of 10:1 to obtain a biochar dielectric material.

[0051] Example 5

[0052] S1: Wash and cut cotton straw into 10 cm long segments, add NaHCO3 and mix, the mass ratio of cotton straw to NaHCO3 is 55:1, then heat from room temperature to 500℃ at a heating rate of 10℃ / min, and carbonize at constant temperature for 2.5h;

[0053] S2: After constant temperature carbonization, the temperature is lowered to room temperature at a rate of 10°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized product BC5;

[0054] S3: The carbide and the additive (a mixture of SiO2 and Al2O3, with a mass ratio of 1.5:0.8) are uniformly mixed in a mass ratio of 10:1 to obtain a biochar dielectric material.

[0055] Example 6

[0056] S1: Clean and cut cotton straw into 10 cm long segments, add NaHCO3 and mix, the mass ratio of cotton straw to NaHCO3 is 55:1, then heat from room temperature to 600℃ at a heating rate of 10℃ / min, and carbonize at constant temperature for 2.5h;

[0057] S2: After constant temperature carbonization, the temperature is lowered to room temperature at a rate of 10°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized BC6;

[0058] S3: The carbide and the additive (a mixture of SiO2 and Al2O3, with a mass ratio of 1.5:0.8) are uniformly mixed in a mass ratio of 10:1 to obtain a biochar dielectric material.

[0059] Experimental Example 1

[0060] Specific surface area determination: In order to analyze the effect of temperature change on the specific surface area of ​​biochar, the specific surface area of ​​the cotton straw biochar solid samples (BC1-6) in Examples 1-6 was determined by a static nitrogen adsorption instrument. The sieved BC1-6 was dried in an oven at 120°C for two hours to reduce the interference of moisture and the like on the test results. The specific surface area data measured at a pressure of 77.35K are shown in Table 1.

[0061] From the data in the table, it can be seen that the specific surface area and adsorption pore volume of BC1, BC2, BC3, BC4, BC5 and BC6 generally show an upward trend with the increase of pyrolysis temperature, among which the biochar prepared at 600°C has the best properties. The total pore volume and average pore size show the same trend, among which the biochar prepared at 500°C has the best properties.

[0062] Table 1 Specific surface area

[0063]

[0064] Experimental Example 2

[0065] Elemental analysis: The C, N and S element contents in the cotton straw biochar solid samples (BC1-6) in Examples 1-6 were determined using an elemental analyzer BELSORP-miniX. The results are shown in Table 2.

[0066] The C content of biochar at different carbonization temperatures is relatively high. When the carbonization temperature increases from 100℃ to 200℃, the N content decreases by 16.40%, the C content increases by 8.10%, and the S content decreases by 31.6%. When the carbonization temperature increases from 200℃ to 300℃, the N content increases by 14.95%, the C content increases by 15.38%, and the S content increases by 130.22%. When the carbonization temperature increases from 300℃ to 400℃, the N content increases by 3.25%, the C content increases by 19.61%, and the S content decreases by 5.21%. When the carbonization temperature increases from 400℃ to 500℃, the N content increases by 5.51%, the C content increases by 7.90%, and the S content decreases by 22.4%. When the carbonization temperature increases from 500℃ to 600℃, the N content increases by 1.49%, the C content increases by 6.13%, and the S content decreases by 7.61%.

[0067] In summary, with the increase of carbonization temperature, the content of S element tends to decrease, and when the carbonization temperature reaches 600℃, the content of S element increases. The content of C and N elements both show an increasing trend. This shows that the organizational form of organic components of cotton straw has changed during the anaerobic pyrolysis process in the box-type atmosphere furnace, and the biochar gradually stabilizes with the breakage of long chains.

[0068] Table 2 Element content of biochar

[0069]

[0070] Experimental Example 3

[0071] Scanning electron microscope analysis: The cotton straw biochar solid samples (BC1-6) in Examples 1-6 were analyzed using a scanning electron microscope. Figure 1 The surface of BC1 shown in the figure presents a pore structure of different sizes, with impurities attached in the pores; the surface of BC2 is mostly irregular honeycomb, with a deformed rectangular structure in cross section, and the small holes on the structure are a small number of pores that appear after the temperature increases; the pore structure of BC3 surface is attached with a large number of small particles of volatile substances, and the accumulation on the cross section is the biochar powder damaged during slicing; BC4 can clearly see that with the increase of temperature, the complete rectangular pore structure is destroyed and a large number of pore structures collapse. It is not difficult to see that the structure of cotton straw biochar is a deformed rectangular and honeycomb pore structure. With the increase of temperature, volatile substances on the surface are precipitated, and the pore structure collapses to varying degrees.

[0072] Experimental Example 4

[0073] XRD analysis: Biochar is usually an amorphous or highly disordered carbon material. The cotton straw biochar solid samples (BC1-6) in Examples 1-6 were subjected to XRD analysis. The results are as follows: Figure 2As shown in the figure, cotton straw is mainly composed of cellulose, hemicellulose and lignin. These organic components will crack and transform in the temperature range of 100-600℃, but will not disappear completely. Through analysis, it was found that BC1 had diffraction peaks at 2θ=14.9° and 2θ=24.4°, which were speculated to be the (101) and (002) crystal planes of cellulose. The stronger diffraction peaks of BC3 were 2θ=14.8°, 2θ=15.3° and 2θ=24.3°. The diffraction peaks corresponded to the (1-01), (101) and (002) crystal planes, which were consistent with the characteristic peaks of cellulose crystal planes. The characteristic peaks at 2θ=28, 29, 30°, 2θ=36° and 2θ=39° corresponded to the (130) and (040) crystal planes, respectively. Among them, (130) may be the structural characteristic peak of amorphous carbon after high-temperature carbonization of biochar. The strong diffraction peaks of BC4 appear at 2θ=15°, 2θ=24°, 2θ=28 and 30°, 2θ=36° and 2θ=39°, which are slightly different from BC1. When the temperature rises to 500°C, the strong diffraction peaks of BC5 appear at 2θ=26, 28 and 29°, 2θ=39 and 40°, and the diffraction peaks correspond to the characteristic peaks of the crystal plane (130) of lignin. The strong diffraction peaks of BC6 appear at 2θ=28 and 29°, 2θ=39 and 40°. Compared with BC3, the characteristic peak of (130) disappears under the temperature change. According to the carbonization temperature and the diffraction peaks of the cellulose crystallization area, it is inferred that as the temperature rises, the cellulose and hemicellulose contained in the cotton straw biochar disappear, and the lignin still exists.

[0074] Experimental Example 5

[0075] Thermogravimetric analysis: In order to analyze the relationship between the dielectric material and thermal stability of biochar components at different temperatures, thermogravimetric tests were conducted. Under nitrogen protection, the temperature was increased at a rate of 10K / min and the test was carried out in the temperature range of 310K-950K.

[0076] The results are as follows Figures 3-4 As shown, the curve of Example 1 is in the first stage from 305K to 368K, the TG curve slowly decreases, the TG curve is relatively flat within 368K-510K, the curve drops sharply after 510K, and a strong, sharp and broad peak appears in the DTG curve. The maximum decomposition rate is reached at 612K, and the final weight loss rate is 70.7%. It is inferred that the cellulose in the biochar undergoes drastic decomposition at this stage.

[0077] The curve of Example 2 is in the first stage from 305K to 368K, the TG curve slowly decreases, the TG curve is relatively flat from 368K to 520K, the curve drops sharply after 520K, and a strong, sharp and broad peak appears in the DTG curve. The maximum decomposition rate is reached at 623K, and the final weight loss rate is 66.7%. It is speculated that this stage is the stage when the cellulose in the biochar undergoes drastic decomposition.

[0078] The curve of Example 3 is in the first stage from 305K to 452K. The TG curve slowly decreases and the DTG curve shows two smaller absorption peaks, which are speculated to be produced by the thermal decomposition of BC1 hemicellulose. The TG curve is relatively flat from 452K to 530K, and the curve drops sharply after 530K. The DTG curve shows a strong and sharp peak and a wide peak. The maximum decomposition rate is reached at 632K, and the final weight loss rate is 55.9%. It is speculated that this stage is the stage of drastic decomposition of cellulose in biochar.

[0079] The curve of Example 4 is in the first stage from 305K to 445K. The TG curve slowly decreases and two smaller absorption peaks appear in the DTG curve, which are presumably produced by the thermal decomposition of part of the hemicellulose in BC2. The TG curve is relatively flat from 452K to 580K, and the curve drops sharply after 580K. A strong and wide peak appears in the DTG curve, and the maximum decomposition rate is reached at 768K. The final weight loss rate is 29.3%, which is the thermal decomposition of cellulose.

[0080] The carbonization temperature of Example 5 is 500°C, and the hemicellulose and part of the cellulose in the cotton straw are basically decomposed. The TG curve is from 305K to 678K as the first stage, and the TG curve tends to be flat. A small endothermic peak appears in DTG at 344K, which is speculated to be a small amount of water in the air adsorbed by BC3. The TG curve begins to decline at 678K, which is speculated to be the thermal decomposition of lignin in BC3. The decomposition rate reaches a maximum value at 842K, and the final weight loss rate is 18.4%.

[0081] The carbonization temperature of Example 6 is 600°C, the TG curve changes gently, and there is a downward trend at 703K. The DTG curve shows an endothermic peak. Due to the high carbonization temperature, both the TG and DTG curves change slowly, and the final weight loss rate is 12.4%. It is speculated that both cellulose and lignin are thermally decomposed within this temperature range. It can be seen from the TG curve and DTG that cellulose and hemicellulose decompose before 400°C, and hemicellulose is more easily decomposed than cellulose. The decomposition temperature of hemicellulose < cellulose < lignin.

[0082] Experimental Example 6

[0083] Dielectric analysis: The biochar dielectric materials obtained in Examples 1 to 6 were tested with a multimeter and were found to be non-conductive. They were polarized under the action of an external electric field. It was speculated that the six carbon materials had interfacial polarization. The reason was that cotton stalks contained a large amount of cellulose and hemicellulose crystallites. There were non-conductive parts inside the crystallites, which caused changes in the effective dielectric constant under the action of an external electric field. Therefore, the biochar dielectric materials obtained in Examples 1 to 6 were cut into blocks of appropriate size, coated with conductive silver glue on both sides, and connected to the IC base through copper wire to form capacitors. The variable temperature-variable frequency dielectric tests were performed in the temperature range of 162K-290K and the frequency range of 500HZ-100KHZ.

[0084] The results are as follows Figures 5 to 11 As shown, the biochar dielectric material prepared in Example 1 has no dielectric anomaly during the cooling process, and there is a step-shaped dielectric anomaly peak during the heating process. Under different electric field strengths, the dielectric constant increases from 10.9 to 14.2. When the frequency is 500HZ, the dielectric constant increases slowly between 160-237K, and the dielectric constant increases suddenly after the temperature rises to 237K, and slowly decreases after 265K. Among them, the dielectric constant of 5KHZ, 10KHZ and 100KHZ remains unchanged as the temperature rises after the temperature reaches 262K.

[0085] The biochar dielectric material prepared in Example 2 has no dielectric anomaly during the cooling process, and there is a step-shaped dielectric anomaly peak during the heating process. Under different electric field strengths, the dielectric constant increases from 2.85 to 3.6, and has a smaller dielectric constant. When the frequency is 500HZ, the dielectric constant increases slowly between 160-240K, and the dielectric constant increases suddenly after the temperature rises to 240K, and slowly decreases after 258K. Among them, the dielectric constant of 5KHZ, 10KHZ and 100KHZ remains unchanged as the temperature rises after the temperature reaches 258K.

[0086] The biochar dielectric material prepared in Example 3 has dielectric anomalies during the cooling process, and the dielectric constant changes in a step-like trend. The dielectric constant does not change significantly between 160-180K, and then the temperature rises, and the dielectric constant increases sharply. After 262K, the dielectric constant tends to be flat. The dielectric constants of 500HZ, 1KHZ, 5KHZ and 10KHZ increase from 30.0 to 90.2 with the increase of temperature. The dielectric constant at 100KHZ frequency does not change before 272K, and the dielectric constant changes after the temperature rises to 273K. It can be used as a room temperature dielectric switch in future electronic devices. There is a step-like dielectric anomaly peak in the heating process, and the dielectric constant increases from 26.4 to 84.1 under different electric field strengths. When the frequency is 500HZ, the dielectric constant increases sharply at 169K, and when the temperature rises to 211K, the dielectric constant tends to be flat. When the frequency is 1KHZ, the dielectric constant increases at 175K, and when the temperature rises to 225K, the dielectric constant tends to be flat. When the frequency is 5KHZ, the dielectric constant increases sharply at 194K, and when the temperature rises to 245K, the dielectric constant tends to be flat. When the frequency is 10KHZ, the dielectric constant increases sharply at 199K, and when the temperature rises to 263K, the dielectric constant tends to be flat. When the frequency is 100KHZ, the dielectric constant increases sharply at 242K, and when the temperature rises to 283K, the dielectric constant tends to be flat. In summary, with the increase of the frequency of the electric field, the critical temperature point where the dielectric becomes abnormal and tends to be flat moves toward the high temperature direction.

[0087] The biochar dielectric material prepared in Example 4 has no dielectric anomaly during the cooling process, and the dielectric constant decreases with the increase of the electric field frequency during the heating process. During the heating process, the dielectric constant increases slowly between 165 and 240 K, and increases suddenly when the temperature rises to 240 K, reaching a peak value at 268 K, and then the dielectric constant shows a decreasing trend as the temperature rises.

[0088] The biochar dielectric material prepared in Example 5 has no dielectric anomaly during the cooling process, and the dielectric constant decreases with the increase of the electric field frequency during the heating process. During the heating process, the dielectric constant does not change between 165 and 245 K, increases suddenly after 245 K, reaches a peak value at 275 K, and then shows a decreasing trend with the increase of temperature.

[0089] The biochar dielectric material prepared in Example 6 has no dielectric anomaly during the cooling process, and the dielectric constant decreases with the increase of the electric field frequency during the heating process. During the heating process, the dielectric constant does not change between 165-245K, increases suddenly after 252K, reaches a peak value at 270K, and then shows a decreasing trend with the increase of temperature.

[0090] In summary, in most cases, the dielectric anomaly of cotton straw biochar dielectric materials with different carbonization temperatures did not occur during low-temperature cooling, but there was dielectric anomaly during low-temperature heating between 165-290K, among which Example 3 showed a step-shaped dielectric anomaly peak, which has potential application in biochar dielectric switches. The dielectric constants of Examples 1-2 and Examples 4-6 all showed a decreasing trend with the increase of the electric field frequency. With the increase of temperature, the dielectric constant first increased to a peak value and then gradually decreased. From the above analysis, it is speculated that the cause of dielectric anomaly is related to the content of hemicellulose and cellulose crystallites in biochar with different carbonization temperatures.

[0091] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing a biochar dielectric material, characterized in that: The following steps are involved: S1: Clean and cut the crop straw into small pieces of 10 cm in length, add NaHCO3 and mix, and pyrolyze for 2 to 3 hours; S2: After pyrolysis, the temperature is lowered to room temperature at a rate of 10-15°C / min, and the crop straw is taken out, crushed, and sieved to obtain carbonized product; S3: Mixing the carbide with the additive to obtain a biochar dielectric material.

2. The method for preparing the biochar dielectric material according to claim 1, characterized in that: The crop straw is cotton straw.

3. The method for preparing the biochar dielectric material according to claim 1, characterized in that: The mass ratio of the crop straw to NaHCO3 is 50-60:

1.

4. The method for preparing the biochar dielectric material according to claim 1, characterized in that: The pyrolysis is carried out by heating the temperature from room temperature to 100-600° C. at a heating rate of 10-15° C. / min.

5. The method for preparing the biochar dielectric material according to claim 1, characterized in that: The mass ratio of the carbide to the additive is 9 to 12:

1.

6. The method for preparing the biochar dielectric material according to claim 1, characterized in that: The additive is a mixture of SiO2 and Al2O3.

7. The method for preparing the biochar dielectric material according to claim 6, characterized in that: The mass ratio of SiO2 to Al2O3 is 1-2:0.5-1.

8. The biochar dielectric material obtained by the method for preparing the biochar dielectric material according to any one of claims 1 to 7.